Navigating small business wellbeing, leadership, and resilience in times of change - Ab Rahman, Farah Adilla (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2025)
This article reviews research on the wellbeing of small business managers, emphasizing how leadership and resilience strategies shape organizational climate during disruptive events like COVID-19. Managerial wellbeing varies across business growth phases: early-stage managers face high workloads and stress, while expansion brings resources, stability, and improved coping. The findings suggest institutional support should be tailored to each growth phase, prioritizing mental health and workload management in the early stages.